The Moderating Role of Firm Size in the Relationship Between Sustainability Reporting, Liquidity, and Financial Performance: Evidence from Indonesian Regional Development Banks - Pamor Nugroho; Bulan Prabawani; Andi Wijayanto (Cita konsultindo, 2026)
The financial performance of Regional Development Banks (BPD) is influenced by internal and external factors that reflect their commitment to sustainability and asset management stability. This study aims to analyze the effect of Sustainability Reports and liquidity on financial performance, with firm size as a moderating variable. A quantitative approach was used, with panel data regression and Moderated Regression Analysis (MRA) methods, implemented in EViews, on the 15 largest asset BPDs in Indonesia during the 2022–2024 period. The results show that Sustainability Reports have a positive and significant effect on financial performance, while liquidity has no significant effect. In addition, firm size is proven to moderate the relationship between Sustainability Reports and financial performance with a negative effect, but does not moderate the relationship between liquidity and financial performance. These findings underscore the importance of optimizing sustainability reporting strategies and resource management within regional development banks to support sustainable financial performance.